ALLEVIATED ANAPHYLACTIC REACTION TO MUSCLE RELAXANTS DUE TO PREOPERATIVE ADMINISTRATION OF CORTICOSTEROIDS - Marković, Danica; Marjanović, Vesna; Vuković, Natalija; Golubović, Mladjan; Milenković, Jelena; Kovačević, Toma; Stanković, Milan (Acta medicae Medianae, 2024)
Anaphylactic reaction during general anaesthesia represents a rare event in clinical practice with a possible fatal outcome. We present a case of a female patient with no prior history of allergic reactions to rocuronium. Shortly after rocuronium administration, she developed the following signs: tachycardia, low blood pressure and bronchospasm. Skin rash and peripheral signs were absent, probably due to previous premedication. Events like this could be potentially fatal if not recognized and treated in time.
Keywords: anaphylaxis, drug hypersensitivity, hypersensitivity, neuromuscular agents, period, perioperative, rocuronium bromide